TAX AVOIDANCE AND EARNINGS MANAGEMENT IN MALAYSIAN FIRMS: IMPACT OF TAX INCENTIVES - Ali, Salsiah Mohd; Norhashim, Mariati; Jaffar, Nahariah (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Understanding the relationship between tax avoidance and earnings management is crucial to evaluating tax policies and ensuring transparent financial reporting. Prior research has highlighted complexities and inconsistent findings, particularly concerning the impact of tax-related reporting incentives. This study addresses these issues by examining the influence of tax incentive recipient status on tax avoidance and earnings management among firms listed on the Kuala Lumpur Stock Exchange (KLSE). It examines whether firms receiving tax incentives from the Malaysian Investment Development Authority (MIDA) exhibit different earnings management behaviours than non-recipient firms. This study employs the effective tax rate (ETR) as a measure of tax avoidance and discretionary accruals (DEM) for earnings management. The dataset includes manually extracted financial information from firms listed on the KLSE for the financial year 2017 and a listing of tax incentive recipient firms from MIDA. Analytical techniques include ANOVA, independent samples t-test, and multiple regression analysis. The findings of this study suggest that higher tax avoidance relates to higher earnings management. Additionally, firms receiving tax incentives exhibit significantly higher ETRs than non-recipients. They are less likely to engage in earnings management, suggesting that tax incentives may deter aggressive financial reporting practices due to compliance pressures. The additional analysis indicates that tax incentives do not significantly moderate the relationship between tax avoidance and earnings management, implying that other pressures still play a crucial role. This study contributes to existing knowledge by emphasizing the need for robust regulatory frameworks that balance economic growth and financial reporting integrity.JEL Classification Codes: H26, M4, M48.